Life of Pi - Martel, Yann. (Waterville, ME : Wheeler Pub., 2003)
Pi Patel, sixteen-year-old son of a zookeeper in Pondicherry, India, sets off with his family to Canada, but his life takes a dramatic turn when their ship sinks in the Pacific leaving him adrift on a raft with a Bengal tiger for company.
Adult
Keywords: Human-animal relationships -- Fiction; Large type books; Ocean travel -- Fiction; Orphans -- Fiction; Storytelling -- Fiction; Survival -- Fiction; Teenage boys -- Fiction; Tigers -- Fiction; Zoo animals -- Fiction; Adventure fiction; Boys -- Fiction; Human-animal relationship -- Fiction; Large print books; Ocean travel -- Fiction; Orphans -- Fiction; Psychological fiction; Storytelling -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Teenagers -- Fiction; Tigers -- Fiction; Zoo animals -- Fiction; Pacific Ocean -- Fiction; Pacific Ocean -- Fiction; Adventure fiction; Psychological fiction